Dayak Onions (Eleutherine americana L Merr) Reduced Mesothelial Cell Detachment After Laparoscopy in Rats - Poerwosusanta, Hery; Yasmina, Alfi; Dewi, Firli Rahmah Primula; Benita, Krist Nathania; Budi, Angga Setya; Putri, Nanda Setya; Ainun, Nur; Fakhriah, Ghyna; Fitri, Anisa; Poerwosusanta, Adam Rahardiyan; Poerwosusanta, Elvira Esmeralda; Aditia, Donny; et al. (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Laparoscopy induces changes and detachment of mesothelial structure. Studies on the prevention of mesothelial cell detachment are rarely found. The Dayak tribe uses the Dayak onion (Eleutherine americana L. Merr) as a wound-healing agent due to its anti-inflammatory and antioxidant activities. This study aimed to prove the anti-inflammatory and antioxidant activities of Dayak onions in preventing mesothelial cell damage after laparoscopy. Materials and methods: Thirty male Sprague-Dawley rats were classified into five groups (n = 6 per group), namely: (a) control, (b) Mediclore, (c) Dayak onion, 30-, (d) 60-, and (e) 90 mg/kg body weight, respectively. The transforming growth factor-beta (TGF-β) and total oxidant status in the peritoneal fluid were determined 24 hours after laparoscopy. Histopathological analysis of mesothelial cell numbers and the protein Zone Occludin-1 (ZO-1) expression in the peritoneum, small intestines, greater omentum, and liver were performed 7 days after the procedure. An in-silico study was conducted to analyze the anti-inflammatory effects of the components of Dayak onions. Results: The in-silico study showed that one of the Dayak onion active compounds, eleutherine, had a potential anti-inflammatory effect and acted as a modulator of TGF-β. Following Dayak onion administration, the TGF- level, the number of mesothelial cell detachments, and ZO-1 expression were all significantly reduced (p<0.05), whereas the total oxidant status (TOS) level was not (p>0.05). Conclusions: Our study showed that Dayak onion administration reduced TGF-β level, number of mesothelial cell detachment, and ZO-1 expression following laparoscopy.